The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1177/1046878114564508
|View full text |Cite
|
Sign up to set email alerts
|

Clarifying Sustainable Development Concepts Through Role-Play

Abstract: The article aims at assessing the effectiveness of a role-play in addressing two concerns: clarifying the concept of sustainable development and teaching sustainable development issues. The effectiveness is gauged by surveying students to reveal how the game matches a set of "significant learning" criteria defined by Fink (2003). Firstly, our article brings a short overview of how the concept of sustainable development has emerged and spread over time. Secondly, in order to assess the learning potential of our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 20 publications
0
19
0
2
Order By: Relevance
“…Barreteau et al (2007) found that their experience with RPGs enhanced exchanges between players beyond the game, seeming to develop social capital in reality through gaming. In contrast, Blanchard and Buchs (2015), found that their game was not overly successful in developing group cohesion and bringing people together.…”
Section: Social Capitalmentioning
confidence: 91%
See 3 more Smart Citations
“…Barreteau et al (2007) found that their experience with RPGs enhanced exchanges between players beyond the game, seeming to develop social capital in reality through gaming. In contrast, Blanchard and Buchs (2015), found that their game was not overly successful in developing group cohesion and bringing people together.…”
Section: Social Capitalmentioning
confidence: 91%
“…D'Aquino et al (2003) game worked to define and identify appropriate stakeholders for participation in land-use decision-making, while Barreteau et al (2007) used games to introduce current stakeholders to new stakeholders. Other games attempted to encourage greater participation, interaction and coordination between stakeholders ( Blanchard and Buchs 2015). However, Morardet et al (2012) highlighted that even within the inclusive embrace of RPGs, power differentials and organisational problems exist, and can and do lead to the exclusion of stakeholders.…”
Section: Cross-scale Interactionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Då rollspel använts med barn i undervisning fann man att det bidrog till att barnen kunde hantera kontroverser mellan olika ståndpunkter, ta ett annat perspektiv än sitt eget, utveckla kritiskt tänkande samt utveckla användandet av språket (Lyle, 2002). Rollspel har också visat sig vara en effektiv metod för att utvidga sina kunskaper kring ett specifikt ämne eller begrepp (Blanchard & Buchs, 2015;Lyle, 2002) och främja meningsfullt och varaktigt lärande samt reflektion hos deltagarna. Att inta en annan persons perspektiv och interagera med andra blir som bränsle för reflektion (Chen & Martin, 2015;Lyle, 2002).…”
Section: Bakgrundunclassified